Respostas
respondido por:
13
Boa tarde
x*(x+10)-5*10=94 ⇒ x²+10x-50=94 ⇒ x²+10x-144=0
Δ = 10² -4*1*(-144) =100+576 = 676 ⇒ √Δ = 26
x= [ -b+-√Δ ) ] / 2*a ⇒ x= [-10+-26 ] / 2 ⇒ x'= -18 (não serve ) e
x'' = 8
Resposta : x = 8
x*(x+10)-5*10=94 ⇒ x²+10x-50=94 ⇒ x²+10x-144=0
Δ = 10² -4*1*(-144) =100+576 = 676 ⇒ √Δ = 26
x= [ -b+-√Δ ) ] / 2*a ⇒ x= [-10+-26 ] / 2 ⇒ x'= -18 (não serve ) e
x'' = 8
Resposta : x = 8
Eduardaraújo1:
Obg
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás